Bus Rapid Transit (BRT) Operations To Reduce Traffic Congestion On Kaligawe Road In Semarang - Rachmat Mudiyono (International Conference on Coastal and Delta Areas, 2017)
Traffic congestion in the city of Semarang is increasing. This is due to the unbalance between the development of road infrastructure and the increasing number of vehicles. Therefore, an orderly, smooth, safe, and convenient mass transportation is needed to reduce congestion. The purpose of this research is to analyze the performance of Bus Rapid Transit (BRT) operation in Semarang City through Kaligawe road. This route is expected to become a reliable public transport in breaking down congestion. The research methodology begins with conducting a Kaligawe road performance survey which is about 4 KM in length, including traffic volume of Semarang-Demak direction of 3.982 emp and the reverse direction of Demak-Semarang is 3.814 emp. While degree of saturation ranged from 0.59 to 0.83. The results of the analysis on BRT found an unbalanced comparison between the capacity of BRT and the volume of traffic passing through the road. The results of this analysis and survey is necessary to maximize the function and work of BRT in several ways ie the location around the shelter must be barrier-free so that BRT can stop at the shelter. there should be a shelter guard who serves as a janitor, security, and information provider about the schedule and about the BRT. The socialization needs to be improved to the public, preferably the holding of Smart Card and feeder transportation, and the holding of tariff reduction in order to increase public interest. Keywords: Performance Analysis, BRT, Kaligawe Road